Migration and Tax Policy: Evidence from Finnish Full-Population Data - Salla Kalin; Ilpo Kauppinen; Kaisa Kotakorpi; Jukka Pirttilä (CESifo GmbH, 2024)
We contribute to the literature on taxation and international mobility by estimating the impact of labour income taxation on the migration decisions of the entire working population in a high-tax source country, Finland. We find that the average domestic elasticity of migration with respect to the domestic tax rate is very small (around 0.0005). We also examine the income gradient of the semi-elasticity of migration, shown to be the key sufficient statistic in Lehmann et al. (2014). Our estimates indicate that the migration semi-elasticities are increasing for top earners, but remain small at least up to top permille of income earners.
Keywords: J61; H31; 330; taxation; migration